ANALISIS COVERAGE WLAN (WIRELESS LOCAL AREA NETWORK) 802.11a MENGGUNAKAN OPNET MODELER - Sukadarmika, Gde; Erawan, Ngurah Indra; Linawati, Linawati; Wendy Saputra, Nyoman (Jurnal Teknologi Elektro; JURNAL TEKNOLOGI ELEKTRO, 2012)
Nowadays, the development tendency of information and communication technology is toward its flexibility and ease of deployment. Cable networks require higher installation cost than wireless network. Therefore, implementation of wireless network, especially a Wireless Local Area Network (WLAN), becomes more popular due to its coverage and flexibility. The 802.11a is the first published WLAN standard from IEEE which offers wide coverage to stationary consumer terminals. In this paper OPNET Modeler Simulator was used to analyze the application standard of 802.11a. Simulation was done to study the characteristic of WLAN 802.11a with several measured parameters such as data dropped (bits/sec), media access delay (sec), delay (sec), and throughput (bits/sec). The simulation was based on the scenario to study the coverage of an access point with the recommended transmitted power, and the effect of data rate on the access point’s